The Delivery of Oral Care Services to Elderly People - Janice Fiske, BDS, FDS, RCS Eng, MPhil (Blackwell Synergy, 2000)
Advances in medical science are enabling people to survive more illness and disability. As people live longer, their mobility andor ability for self-care often are reduced by physical or mental disability and other chronic diseases. It may become unreasonable or impractical for them to access mainstream dental services. Increasing numbers of dentate elderly people with expectations of oral health higher than earlier cohorts of elderly people are likely to bring increasing demands to the dental profession for their continuing care. Thus, the oral care for disabled elderlypeople in noninstitutionalized settings may pose a challenge. The oral care options available to this group of people include the dental surgery/operatory, a mobile dental service, home-based or domiciliary dental care, a mix-and-match combination of surgery-based and domiciliary care, and cyberspace. Noninstitutionalized, disabled elderly people may have to rely on domiciliary care services for their oral health care.